Down-regulation of miR-556-3p inhibits hemangioma cell proliferation and promotes apoptosis by targeting VEGFC - Jin, Wen; Chen, Liang; Gao, Fengyun; Yang, Mei; Liu, Yan; Wang, Bo (Cellular and Molecular Biology, 2020)
The purpose of this study was to determine the effect of microRNA (miR)-556-3p on cell proliferation and apoptosis of hemangioma-derived endothelial cells (HemECs). qRT-PCR was used to compare the expressions of miR-556-3p in HemECs and normal cells. The target gene was identified using dual-luciferase reporter assay. Cell proliferation was measured with MTT assay, while western blotting was used to assay VEGFC expression levels. Apoptosis was assayed with FITC Annexin V Apoptosis assay kit. miR-556-3p was overexpressed in HemECs. Transfection with miR-556-3p inhibitor resulted in decreased proliferation of HemECs (p<0.05). The expression of the target gene of miR-556-3pi.e. VEGFC was upregulated when miR-556-3p inhibitor was transfected. The transfection also resulted in increased apoptosis. In HemECs, miR-556-3p is overexpressed and VEGFC expression is low. Thus, miR-556-3p or VEGFC might be potential targets for treatment of angiosarcoma.